Analisis Risiko Produksi Sayuran Daun Indigenous di Kecamatan Kadudampit, Kabupaten Sukabumi, Jawa Barat - Mubarokah, Syaima Lailatul; Nahraeni, Wini; Yusdiarti, Arti; Rahayu, Arifah (JURNAL AGRIBISAINS, 2017)
This study aims to identify 1) the source of production risk in some indigenous leaf vegetables, especially basil 2) the level of risks encountered, and 3) formulate strategies tocontrol the risk of production of indigenous leaf vegetable. The research was conducted in Kecamatan Kadudampit Sukabumi, the method of sampling used simple random sampling.The number of farmers were 42 farmers. In specialization activities, the method to process risk data used are analysis of variance, standard deviation and coefficient of variation. Theresults showed that the source of production risk faced by farmers were weather / climate, pest and disease diseases and seed quality. The expected return value of basil commodityRp.1.801.204 with the risk level of losses was 0.382 or 38%. Strategies that could be done to reduced the risk was the diversification activity with . timing and appropriate commodities of diversification activities, plan intercropping cropping pattern between two combination basil with lettuce were 60% and 40% and basil with gourd were 60% and 40%, risk managementin production through preventive strategies with improvement of physical facilities and mitigation strategies with pest and disease controls encountered.Keywords: basil, variance analysis, standard deviation, coefficient of variation, risk management.